Human infections due to nontuberculous mycobacteria: the infectious diseases and clinical microbiology specialists' point of view. (September 2015) - Guglielmetti, Lorenzo; Mougari, Faiza; Lopes, Amanda; Raskine, Laurent; Cambau, Emmanuelle
Nontuberculous mycobacteria (>150 species such as Mycobacterium avium, Mycobacterium kansasii, Mycobacterium chelonae and Mycobacterium abscessus ) are opportunistic pathogens causing lung and extrarespiratory infections, beside M. ulcerans and M. marinum that are pathogens causing specific skin and soft tissue infections. Disseminated infections occur only in severe immunosuppressed conditions such as AIDS. The diagnosis is based on repeated isolations of the same mycobacterium associated with clinical and radiological signs, and the absence of tuberculosis. Precise species identification is obtained by molecular biology. Therapeutic antibiotic regimens differ with regard to the mycobacterial species that are involved. Prevention of iatrogenic infections relies on using sterile water in all injections, healthcare and cosmetic occupations. Future perspectives are to set effective antibiotic regimens tested in randomized therapeutic trials.